Branding Strategy "The Light Of Aceh" Through E-Tourism On Sustainable Tourism Development in Aceh Province - Khalida Ulfa; Muchamad Zaenuri; Dian Eka Rahmawati; Saddam Rassanjani; Mukhrijal Mukhrijal; Ayu Imanullah (Journal of Governance and Public Policy, 2021)
One of the latest strategies in Indonesia in developing tourism is E-Tourism, a digital platform that provides convenience for foreign and domestic tourists. This study aims to determine the Branding Strategy "The Light Of Aceh" through E-Tourism in Sustainable Tourism Development in Aceh Province and its inhibiting factors. The research data comes from primary and secondary data related to the research focus. The data analysis technique used the Nvivo 12 plus analysis using crosstab through the chart and sociogram features. The results showed that the Branding strategy "The Light Of Aceh" through E-Tourism in sustainable tourism development uses 4 strategies, namely POSE (Paid Media, Owned Media, Social Media, and Endorser). Of the four strategies, the highest percentage is through social media digital platforms which are the most strategic in promoting tourism. The inhibiting factor is in terms of human resources that are still minimal, in terms of infrastructure that has not been managed properly in several tourist destinations, and the social conditions of the community are still minimal related to public awareness of managing tourist destination places properly so it is very important to support tourism actors to return or whether or not to Aceh for a tour.